Variations and anomalies in the structure and branching of lumbosacral spinal nerve roots: a case report and global insights - Nekhlopochyn, O. S.; Verbov, V. V.; Leshko, M. M.; Cheshuk, Ye. V.; Ivanovych, I. M.; Malysheva, T. A. (Modern medical technology, 2023)
Aim. The objective of this study is to analyze the clinical course of lumbosacral spinal nerve root anomalies / variants Type I according to the A. Neidre and I. MacNab’s classification, along with a retrospective MRI data analysis before surgery, focusing on the unique branching and topography of the spinal nerve roots. Additionally, we aim to address the relevance of correlating preoperative visualized features with the presence of anatomical anomalies attributed to these spinal nerve root variations, and their implications on the clinical presentation. Our study aims to compare our findings with the global diagnostic experience, classification, and specific aspects of performing discectomies based on individual anatomical characteristics of the lumbosacral region. Results. We present data from our own observation, when during surgery, a probable verification of a Type I lumbosacral spinal nerve root anomaly / variation according to the A. Neidre and I. MacNab’s classification was discovered in a patient. The anomaly appeared as a dense mass resembling a nerve root in the structural characteristics but with a significantly larger diameter. It emerged from the dural space at the level of the upper third of the L5 arch and then divided into two parts. A thinner bundle, comparable in diameter to a normal nerve root, exited through the L5-S1 intervertebral foramen, while a considerably thicker bundle followed a path parallel to the axis of the dural sac and exited through the S1-S2 intervertebral foramen. Comparison with global clinical observations revealed that despite the significant clinical and surgical implications, several aspects of this anomaly remain poorly studied and require further exploration and systematization. Conclusions. The lumbosacral nerve root anomalies (LSNRA) demonstrate a variety of structural variations and branching patterns, which are reflected in different classifications. Among the professional community, the classification of LSNRA, developed by A. Neidre and I. MacNab in 1983 and supplemented by S. M. Burke et al. in 2013, is recognized as the most relevant and frequently applied. While changes in vertebral bone structures can be easily diagnosed using modern imaging methods, preoperative diagnosis of LSNRA proves to be challenging, and the informativeness of standard MRI is limited, as confirmed by the clinical case presented. The dissonance between prominent neurological symptoms and relatively minor disc protrusion allows for the potential presence of a root variation/anomaly when planning the lumbar spine discectomy. The most informative diagnostic method for LSNRA is MR neurography. Among the radiological signs of Type I lumbоsacral nerve root anomalies, the following are considered valid: “corner sign”, “fat crescent sign”, and “parallel sign”. The verification of LSNRA is predominantly intraoperatively based on a series of characteristic topographicanatomical features, including atypical locations of the root’s origin from the dural sac, “unusual” nerve root exit angle, even up to a right angle, and technical challenges in root mobilization during routine lumbar discectomy procedures.